Creating the customer-driven library : building on the bookstore model - Woodward, Jeannette A. (American Library Association, 2005)
Aiming to help libraries market their services using low-cost or no-cost techniques, Woodward shares practical lessons for any library's revitalization inspired by the success of mega bookstores. Bookstores focus on the customer, and libraries need to take a page from their book.